2007
DOI: 10.1108/02640470710741296
|View full text |Cite
|
Sign up to set email alerts
|

Enriching e‐learning metadata through digital library usage analysis

Abstract: PurposeIn this paper we propose an evaluation framework for analyzing learning objects usage, with the aim of extracting useful information for improving the quality of the metadata used to describe the learning objects, but also for personalization purposes, including user models and adaptive itineraries. MethodologyWe present experimental results from the log usage analysis during one academic semester of two different subjects, 350 students. The experiment looks into raw server log data generated from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…From the system viewpoint, digital media, which have become commonplace with university students and educators, can enrich the teaching and learning experiences (Liaw et al , 2007) and academic libraries also can support e‐learning implementation (Sharifabadi, 2006). Therefore, the growing need of continuous education and the inclusion of new multimedia technologies have become crucial factors for this expansion (Ferran et al , 2007). An academic library, faculty, and academic development department managing e‐learning may use appropriate technologies to facilitate learning and access to resources and services.…”
Section: Introductionmentioning
confidence: 99%
“…From the system viewpoint, digital media, which have become commonplace with university students and educators, can enrich the teaching and learning experiences (Liaw et al , 2007) and academic libraries also can support e‐learning implementation (Sharifabadi, 2006). Therefore, the growing need of continuous education and the inclusion of new multimedia technologies have become crucial factors for this expansion (Ferran et al , 2007). An academic library, faculty, and academic development department managing e‐learning may use appropriate technologies to facilitate learning and access to resources and services.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an analysis of the usage of objects deposited in the repository allows metadata to be continuously enhanced (Ferran et al, 2007) by identifying and correcting labelling problems. An item is a useful set of content and metadata, added during the ingest process or later.…”
Section: Dspacementioning
confidence: 99%
“…It is advisable to have two versions of various materials: one accessible to the public for versioning and usage data collection (Ferran et al, 2007), and one set aside for managers for long-term preservation, though both are linked via metadata. So, for example, the tags in a PDF/A file should be carefully checked to validate that the file format is correct and consistent.…”
Section: Significant Propertiesmentioning
confidence: 99%
“…Farran et al (2007) conducted an empirical study, with a sample of 350 students, to address the relationship between user profiles and information seeking behavior in e‐learning environments. Results of the study reported evidence of the use of digital library resources as well as external information sources.…”
Section: Literature Reviewmentioning
confidence: 99%